2007
DOI: 10.1099/mic.0.2006/001206-0
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology of biomining: development and optimization of mineral-oxidizing microbial consortia

Abstract: Biomining, the use of micro-organisms to recover precious and base metals from mineral ores and concentrates, has developed into a successful and expanding area of biotechnology. While careful considerations are made in the design and engineering of biomining operations, microbiological aspects have been subjected to far less scrutiny and control. Biomining processes employ microbial consortia that are dominated by acidophilic, autotrophic iron-or sulfur-oxidizing prokaryotes. Mineral biooxidation takes place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
239
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(250 citation statements)
references
References 48 publications
2
239
0
9
Order By: Relevance
“…The inoculation of pure microbial strains or consortia has been proposed [23][24][25], but up to now this has not been a common practice. During heap operation, a great diversity of microbes are present, mostly bacteria and archaea [26][27][28]. The most well-known and first identified bioleaching bacteria are Acidithiobacillus ferrooxidans, Leptospirillum ferrooxidans, and Acidithiobacillus thiooxidans.…”
Section: Operating Factors Affecting the Bioleaching Processmentioning
confidence: 99%
“…The inoculation of pure microbial strains or consortia has been proposed [23][24][25], but up to now this has not been a common practice. During heap operation, a great diversity of microbes are present, mostly bacteria and archaea [26][27][28]. The most well-known and first identified bioleaching bacteria are Acidithiobacillus ferrooxidans, Leptospirillum ferrooxidans, and Acidithiobacillus thiooxidans.…”
Section: Operating Factors Affecting the Bioleaching Processmentioning
confidence: 99%
“…They can oxidize ferrous iron, RISCs such as tetrathionate, thiosulfate and elemental sulfur, as well as sulfide minerals in the presence of 0.02% yeast extract. Because of the versatile metabolism and tolerance to a hostile environment characterized by low pH and high metal concentrations, the genus Sulfobacillus has been considered for optimization of microbial consortia [10], and they are crucial in mixed cultures during leaching. It is reported that the smaller proportion of Sulfobacillus in leaching consortia under continuous conditions was correlated with the reduction of chalcopyrite leaching kinetics than in batch mode.…”
Section: Introductionmentioning
confidence: 99%
“…The acid mine drainage (AMD) environment has been established as a model ecosystem, due in part to microbial compositional characteristics that make the biofilms tractable for cultivation-independent molecular analyses (reviewed by Denef et al, 2010b). AMD and other acidic environments have also been extensively studied due to their importance in acid and metal contamination, and application in the biomining industry (reviewed by Rawlings and Johnson, 2007;Gadd, 2010).…”
Section: Introductionmentioning
confidence: 99%